L’empatia nascosta: un orizzonte possibile - D'Agata, Valeria Costanza (Bollettino Filosofico, 2022)
This article aims to emphasise the pre-reflective embodied dimension which constitutes the foundation of emotional attunement with others and to discover if, in individuals affected by inter-subjectivity disorders, such as the Asperger syndrome or autistic spectrum condition, would it be possible to recognise a hidden implicit type of empathy, which manifest its diverse way of approaching the world. Keywords: Affective Attunement, Autism, Empathy, Fuchs, Körper/Leib